The nature and art of workmanship - Pye, David 1914- (Bloomsbury Academic, 2015)
"The Nature and Art of Workmanship explores the meaning of skill and its relationship to design and manufacture. Cutting through a century fuzzy thinking, David Pye proposes a new theory of making based on the concepts of 'workmanship of risk' and 'workmanship of certainty'. And he shows how good workmanship imparts all-important diversity to our visual environment." -- Provided by publisher